Bibliometric analysis of scientific production on digital marketing (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
Digital marketing contributes to create a competitive advantage for national and international commerce. The objective is to analyze the trend of scientific production on digital marketing at a global level, using bibliometric indicators. The results present production, visibility, impact and collaboration indicators. Identifying a sustainable and exponential rate of production, the country with significant levels of publications is in quartile 4, the prevalent keywords are "Digital Marketing", "Social Media" and "Marketing", is the United States. It is concluded that the bibliometric analysis provides information on the products generated from the different territories where they are produced, which becomes important elements for business, public and social decision making.